Assessment of the Need to Integrate Academic Electronic Medical Records Into the Undergraduate Clinical Practicum: A Focus Group Interview. Issue 6 (June 2016) - Choi, Mona; Park, Joon Ho; Lee, Hyeong Suk
Abstract : As healthcare systems demand that nurses be competent in using electronic medical records for patient care, the integration of electronic medical records into nursing curricula has become necessary. The purpose of this study was to explore how students, new nurses, clinical instructors, and faculty perceive the integration of academic electronic medical records into the undergraduate clinical practicum. From January to February 2014, four focus group interviews with 18 participants were conducted based on purposive sampling. Content analysis was used on the unabridged transcripts to extract themes and develop meaningful categories. Three major themes and eight subthemes were revealed from the focus group interviews. The major themes were "electronic medical record as a learning tool for clinical practicum, " "essential functions of academic electronic medical records, " and "expected outcomes of academic electronic medical record." Participants expected academic electronic medical records to enhance students' nursing informatics competencies. The findings of this study can inform the process of developing academic electronic medical records for clinical practicum, which will then augment students' informatics competencies.